COMPARATIVE ANALYSIS OF METAL NANOPARTICLES SYNTHESIZED FROM HIBISCUS ROSA SINESIS AND THEIR ANTIBACTERIAL ACTIVITY ESTIMATION AGAINST NINE PATHOGENIC BACTERIA - Tyagi, Shruti; Kumar, Arvind; Tyagi, Pankaj K (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study demonstatesÂ a simple, cost effective protocolÂ for biosynthesis of stable silver (Ag) and gold (Au) nanoparticles from Hibiscus Rosa sinesis and their comparison by applying antibacterial activities against nine pathogenic bacterial species. Methods: Silver (Ag) and gold (Au) nanoparticles were biosynthesized from Hibiscus Rosa sinesis were characterized by UVâ€“VIS spectroscopy, FTIR and TEM. The antibacterial activities Â of AgNPs Â and AuNPs were evaluated againstÂ 9 pathogenic bacterial species Â Pseudomonas aeroginosa, Bacillus subtilis Micrococcus luteus, Staphylococcus aureus, Staphylococcus epidermidis, Enterobacter aerogens, Escherichia coli, Streptococcus pneumoniae, Aeromonas hydrophila by the agar disc diffusion method. Results: Synthesized AgNPs Â were obtained in 13.01 to 28.14 nm size range, while AuNPs were in Â 6.32 to 18.19 nm size range. The results of Fourier transform infrared spectroscopy (FTIR) spectra indicates Â that the AuNPs are bound to amine groups and the AgNPs to carboxylate ion groups. The antibacterial activities Â of AgNPs,Â the zone of inhibition significantly increased with the Â increases of concentrations of AgNPs in all pathogenic bacterial species Â except Â in the case of S. epidermidis at 50%, S. aerogenes and A. hydrophila at 70%, while in case of AuNPs antibacterial activityÂ was displayedÂ only against B. subtilis at 20% and 100% concentration. Conclusion: This study suggests that AgNPs exhibits outstanding antibacterial activity against pathogenic bacteria as compared to AuNPs synthesized from Hibiscus Rosa sinensis leaf extract and insights to their potential applicability as an alternative antibacterial Â agent in microbial and human health system to reduce the resistance ability of pathogenic bacteria.Â Â Â